Doped Sr2FeIrO6—phase separation and a Jeff ≠ 0 state for Ir5+ - Page, J; Topping, C; Scrimshire, A; Bingham, P; Blundell, S; Hayward, M (American Chemical Society, 2018)
High-resolution synchrotron X-ray and neutron powder diffraction data demonstrate that, in contrast to recent reports, Sr2FeIrO6 adopts an I1̅ symmetry double perovskite structure with an a–b–c– tilting distortion. This distorted structure does not tolerate cation substitution, with low levels of A-site (Ca, Ba, La) or Fe-site (Ga) substitution leading to separation into two phases: a stoichiometric I1̅ phase and a cation-substituted, P21/n symmetry, a–a–c+ distorted double perovskite phase. Magnetization, neutron diffraction, and 57Fe Mössbauer data show that, in common with Sr2FeIrO6, the cation substituted Sr2–xAxFe1–yGayIrO6 phases undergo transitions to type-II antiferromagnetically ordered states at TN ∼ 120 K. However, in contrast to stoichiometric Sr2FeIrO6, cation substituted samples exhibit a further magnetic transition at TA ∼ 220 K, which corresponds to the ordering of Jeff ≠ 0 Ir5+ centers in the cation-substituted, P21/n symmetry, double perovskite phases.